1987
DOI: 10.1042/bj2440443
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisomal localization of glucose-6-phosphate dehydrogenase and pyrophosphate-stimulated dihydroxyacetone-phosphate acyltransferase in mouse kidney

Abstract: 1. The subcellular localization of dihydroxyacetone-phosphate acyltransferase (DHAPAT) (assayed in the presence of pyrophosphate) and glucose-6-phosphate dehydrogenase (NADP+-dependent) activity in mouse kidney was investigated by density-gradient centrifugation. 2. DHAPAT has a predominantly peroxisomal distribution, and the activity in purified peroxisomes is stimulated by various organic and inorganic phosphate-containing compounds. The pH optimum is acid. 3. Approx. 10% of the cellular NADP+-dependent gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…Results obtained in this work showed that the proportion of each G6PDH and 6PGDH activities in peroxisomes, cytosol and chloroplasts of pea leaves was about 10, 10 and 80 %, respectively (results not shown). The proportion of G6PDH in peroxisomes agrees with that reported for cellular fractions of mouse kidney, where 10 % of the total G6PDH activity was also found in peroxisomes [63].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Results obtained in this work showed that the proportion of each G6PDH and 6PGDH activities in peroxisomes, cytosol and chloroplasts of pea leaves was about 10, 10 and 80 %, respectively (results not shown). The proportion of G6PDH in peroxisomes agrees with that reported for cellular fractions of mouse kidney, where 10 % of the total G6PDH activity was also found in peroxisomes [63].…”
Section: Discussionsupporting
confidence: 89%
“…The EM immunocytochemical results reported in this paper confirmed the localization of G6PDH in pea leaf peroxisomes. In animals, the peroxisomal localization of G6PDH in mouse kidney [63] and in rat liver [47] has been reported. However, to our knowledge, the EM immunocytochemical localization of G6PDH has not been carried out thus far for any organism.…”
Section: Discussionmentioning
confidence: 99%
“…There are other enzymes besides IDH1 present in the cytosol of the cell that can form NADPH, such as malic enzyme 1 and glucose-6-phosphate dehydrogenase. Although glucose-6-phosphate dehydrogenase enzyme activity has been detected in peroxisomes [29, 30], its concentration in peroxisomes might be lower than that of IDH1. Its C-terminus sequence tripeptide (histidine-lysine-leucine) suggests that, compared to the C-terminus tripeptide sequence of the IDH1 protein (alanine-lysine-leucine), it would be a poor ligand for PEX5, a receptor that functions to import proteins into peroxisomes [31, 32].…”
Section: 0 Discussionmentioning
confidence: 99%
“…This indicates that the microsomal fraction contains a DHAPAT enzyme different from the peroxisomal enzyme, and that the mitochondrial enzyme activity may derive from peroxisomal fragments. This view is shared by Patel et al (1987) andSkorve et al (1990). Jones & Hajra (1977) found that in guinea-pig liver the DHAPAT activity is present only in peroxisomes, in contrast with rat liver, where it is present also in microsomes.…”
Section: Discussionmentioning
confidence: 94%